Is It Possible to Recognize Cervical Artery Dissection on Stroke Brain MR Imaging? A Matched Case-Control Study - Naggara, O.; Soares, F.; Touze, E.; Roy, D.; Leclerc, X.; Pruvo, J.-P.; Mas, J.-L.; Meder, J.-F.; Oppenheim, C. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Extracranial CAD accounts for nearly 20% of cases of stroke in young adults. The mural hematoma frequently extends cranially to the petrous carotid segment in cCAD or is distally located in vCAD. We hypothesized that standard brain MR imaging could allow the early detection of CAD of the upper portion of carotid and vertebral arteries. MATERIALS AND METHODS: Our prospectively maintained stroke data base was retrospectively queried to identify all patients with the final diagnosis of CAD. In the 103 consecutive patients studied, analysis of cervical fat-suppressed T1-weighted sequences demonstrated that the mural hematoma was located in the FOV of brain MR imaging in 77 patients. Subsequent to enrollment of a patient, a control patient was extracted from the same data base, within a similar categories for sex, age, NIHSS score, and stroke on DWI. Two blinded observers independently reviewed the 5 brain MR sequences of each examination and determined whether a CAD was present. RESULTS: Fifty-nine of the 77 patients with CAD (76.6%) and 73 of the 77 patients without CAD (94.8%) were correctly classified. Brain MR imaging demonstrated cCAD more frequently than vCAD in 54/58 (93.1%) and 5/19 (26.3%) patients, respectively, (P < .0001). CONCLUSIONS: Initial brain MR imaging can correctly suggest CAD in more than two-thirds of patients. This may have practical implications in patients with stroke with delayed cervical MRA or in those who are not initially suspected of having CAD. CADcervical artery dissectioncCADcarotid artery dissectionCEcontrast-enhancedDSAdigital subtraction angiographyDWIdiffusion-weighted imagingFLAIRfluid-attenuated inversion recoveryICAinternal carotid arteryINSERMInstitut National de la Santé et de la Recherche MédicaleMRAMR angiographyMRIMR imagingNIHSSNational Institutes of Health Stroke ScalePWIperfusion-weighted imagingSTARDStandards for Reporting of Diagnostic AccuracyTIAtransient ischemic attackvCADvertebral artery dissection